Enteral feeding in head and neck cancer patients at a UK cancer centre. Issue 5 (5th February 2013) - Sheth, C. H.; Sharp, S.; Walters, E. R.
Abstract Background Patients undergoing radiotherapy or chemoradiotherapy treatment for head and neck cancer have an increased risk of malnutrition, and may require enteral feeding via nasogastric or gastrostomy tube. The aim of this audit was to examine current enteral feeding practice, mortality, morbidity and 6‐month outcome data of head and neck cancer patients receiving radical (chemo)radiotherapy at a regional cancer centre and to compare the results with a regional head and neck cancer gastrostomy audit. Methods A 2‐year audit was conducted (2006–2008). Inclusion criteria were all adult patients diagnosed with squamous cell carcinoma of the head and neck, receiving radical radiotherapy or chemoradiotherapy treatment. The first‐year data were collected retrospectively, and the second‐year data were collected prospectively. Data were collected on all patients requiring enteral feeding with 6‐month outcome data relating to route of nutrition. Results Approximately 14% (n = 32/223) of patients were admitted for nasogastric feeding as a result of inadequate oral alimentation. On admission, 94% were at risk of refeeding syndrome, taking a mean (SD) of 11 (4.9) days to reach full nutritional requirements. Mean (SD) length of hospital stay was 13 (5.1) days. No major complications from nasogastric tube insertion were found. The mean (SD) length of nasogastric feeding was 72 (20.1) days with 89.6% managing full nutritional requirements orally at 6 months. Conclusions Patients requiring enteral feeding during treatment were fed via a nasogastric tube, rather than via a prophylactic gastrostomy tube. Compared with the regional gastrostomy audit results, our patients had a lower clinical risk/complication rate, with a greater proportion tolerating full oral intake at 6 months. Therefore, nasogastric feeding, rather than prophylactic gastrostomy tube feeding, could be a more appropriate method of enteral feeding in this patient group.